117k views
5 votes
If f(x) = 6x – 4, then f^-1(x)=

User Swydell
by
5.4k points

1 Answer

2 votes

Answer:


f^(-1)(x)=(x)/(6)+(2)/(3)

Explanation:

Given function.


f(x)=6x-4

To find the inverse function
f^(-1)(x)

Step 1:

Replace
f(x) with
y in the function.


y=6x-4

Step 2:

Interchange
y with
x in the equation.


x=6y-4

Step 3:

Solve for
y.

We have
x=6y-4

Adding 4 to both sides,


x+4=6y-4+4


x+4=6y

Dividing each term by 6 to isolate
y


(x)/(6)+(4)/(6)=(6y)/(6)


(x)/(6)+(4)/(6)=y

Simplifying fractions by dividing the numerator and denominator by their GCF.


(x)/(6)+(4/ 2)/(6/ 2)=y


(x)/(6)+(2)/(3)=y

Thus the equation of
y is:


y=(x)/(6)+(2)/(3)

Step 4:

Replace
y with
f^(-1)(x)


f^(-1)(x)=(x)/(6)+(2)/(3) (Answer)

Thus, we have the inverse function

User David Fawzy
by
5.2k points